ปัจจัยคัดสรรที่สัมพันธ์กับกลุ่มอาการขาอยู่ไม่สุขขณะพักของผู้ป่วยไตวายเรื้อรังระยะสุดท้ายที่ได้รับการฟอกเลือดด้วยเครื่องไตเทียม - เบญจมาศ แสงสว่าง (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This descriptive study aimed to investigate relationships among duration of dialysis, co-morbidity, body mass index, calcium level, hemoglobin level, insomnia, depression, obstructive sleep apnea and restless leg syndrome in patients with end stage renal disease receiving hemodialysis. One hundred and one end stage renal disease patients on hemodialysis were recruited using a simple random technique.  The participants followed up at the Nephrology clinic of Phra Nakhon Si Ayutthaya Hospital and Saraburi Hospital. The research instruments consisted of: 1) the demographic and clinical data questionnaire, 2) the health status questionnaire, 3) the severity of restless leg syndrome questionnaire, 4) the insomnia severity Index, 5) the beck depression inventory II, and 6) the stop-bang questionnaire. Content validity was examined by five experts. Reliability were 0.84, 0.89, 0.89 and 0.73, respectively. Data were analyzed using mean, standard deviation, and Pearson’s product moment correlation, Spearman rank correlation coefficient, and Eta.The major findings were as follows.1. Mean score of severity of restless leg syndrome in end stage renal disease patients receiving hemodialysis was at moderate level (X=13.91, SD=9.74)2. Diabetes mellitus, body mass index, insomnia, depression, and obstructive sleep apnea were positively, statistically associated with restless legs syndrome in end-stage renal disease patients receiving hemodialysis at the level of 0.05 (r=0.249, 0.213, 0.521, 0.416 and 0.222, respectively) Hypertension, dyslipidemia, duration of dialysis, calcium level, hemoglobin level were not positively correlated with restless legs syndrome in end-stage renal disease patients receiving hemodialysis.